2004
DOI: 10.1007/s00445-003-0296-8
|View full text |Cite
|
Sign up to set email alerts
|

Stratovolcano stability assessment methods and results from Citlalt�petl, Mexico

Abstract: CitlaltØpetl volcano is the easternmost stratovolcano in the Trans-Mexican Volcanic Belt. Situated within 110 km of Veracruz, it has experienced two major collapse events and, subsequent to its last collapse, rebuilt a massive, symmetrical summit cone. To enhance hazard mitigation efforts we assess the stability of CitlaltØpetl's summit cone, the area thought most likely to fail during a potential massive collapse event. Through geologic mapping, alteration mineralogy, geotechnical studies, and stability model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…Such a condition has been recognized as capable of rendering a volcano more prone to collapse (Lopez and Williams 1993;Reid et al 2001;Zimbelman et al 2004;Opfergelt et al 2006), and indeed, it played a determining role in the events described in the following sections.…”
Section: The Southeast Crater Before the 2006 Eruptionsmentioning
confidence: 96%
“…Such a condition has been recognized as capable of rendering a volcano more prone to collapse (Lopez and Williams 1993;Reid et al 2001;Zimbelman et al 2004;Opfergelt et al 2006), and indeed, it played a determining role in the events described in the following sections.…”
Section: The Southeast Crater Before the 2006 Eruptionsmentioning
confidence: 96%
“…These include applying Limit Equilibrium Methods (LEM) (Voight et al, 1983;Iverson, 1995;Elsworth and Voight, 1996;Hürlimann et al, 2000;Reid et al, 2000;Donnadieu et al, 2001;Okubo, 2004;Apuani and Corazzato, 2010) and numerical modeling by Distinct Element Methods (DEM) (Zimbelman et al, 2004), Finite Difference Methods (FDM) (Hürlimann et al, 2000;Apuani et al, 2005aApuani et al, ,b, 2007Apuani and Corazzato, 2010) and Finite Element Methods (FEM) (Sousa and Voight, 1995;Apuani and Corazzato, 2010;del Potro et al, 2013;Schaefer et al, 2013). However, numerical data on the relevant mechanical properties for volcanic rocks and rock masses used in these types of studies remain a major source of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The largest areas affected are located at the northwestern edge of the horseshoe-shaped crater and on the northwestern flanks of San Antonio volcano. Considering that this region has 4,000 mm of rain per year, these zones may be prone to future rock slides and major landslides, as have been observed elsewhere (Zimbelman et al 2004). …”
Section: Post-collapse Activitymentioning
confidence: 93%
“…Collapse potential can be enhanced by structural factors such as interbedded lavas and pyroclastic deposits (Leonov 1995;Vallance et al 1995;Carrasco-Núñez et al 2006), the intrusion of dikes (Siebert 1984;Siebert et al 1987;Elsworth and Voight 1995), intersecting rift zones (Carracedo 1996), gravitational spreading of the volcano substrate (van Wyk de Vries and Francis 1997), faults (Hall et al 1999;Ventura et al 1999;van Wyk de Vries et al 2003), tectonic movement (Francis and Self 1987;Carracedo 1996;Tibaldi 1995), and hydrothermal alteration of the summit (López and Williams 1993;Zimbelman et al 2004). Siebert (1984) concluded that failure of semiconical volcanoes takes place perpendicular to the maximum principal stress in the region.…”
Section: Introductionmentioning
confidence: 98%